Розвиток систем електронної комерції та електронного бізнесу в умовах невизначеності та ризику - Макарова, М.В. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The article describes the theoretical and methodical approaches to the challenges of E-commerce systems (SEC) and E-business systems (SEB) under conditions of uncertainty and risk.